PENGARUH KESENANGAN (PLEASURE), KEGAIRAHAN(AROUSAL) DAN DOMINASI (DOMINANCE) TERHADAP PEMBELIAN TIDAK TERENCANA (STUDI KASUS PADA KONSUMEN CARREFOUR CITRA GARDEN MEDAN) - MARIA KRISTINA SITUMORANG (JURNAL REGIONOMIC, 2018)
This research aims to determine and explain the influence of pleasure, arousal and dominance toimpulsive buying at shopping centre Carrefour Citra Garden Medan. This research uses a populationof 267 visitors, and a sample of 73 people who shop at Carrefour Citra Garden Medan. Data collectiontechniques used are through a questionnaire which measurements using Likert scale. Analyticaltechniques used are Path Analysis which makes it easier to see the role of pleasure, arousal anddominance to impulsive buying. Test results show that pleasure, arousal and dominance to impulsivebuying influenced the impulsive buying behaviour at shopping center Carrefour Citra Garden Medan.